Effectiveness Of Ciplukan Stem Water Extract (Physalis Minima L.) On Malondialdehyde Levels Of Mandibular Bones Of White Rats (Rattus Norvegicus) Wistar Strain Post Ovariectomy - Fadhilah, Nadia; Permatasari, Nur; Widodorini, Trining (Indonesian Health Journal, 2025)
Estrogen functions as an antioxidant that can suppress free radicals. Hypoestrogenic conditions will increase oxidative stress. Periodontitis is a disease related to oxidative stress. The occurrence of oxidative stress is characterized by increased levels of malondialdehyde (MDA). Malondialdehyde is commonly used to assess oxidative stress. Phytoestrogens are components of plants that have biological activity similar to estrogen. Ciplukan plants are suspected to be phytoestrogen compounds. Based on theoretical studies, it is suspected that the ciplukan stem contains physalin, which has a similar effect to the action of estrogen. The purpose of this study was to determine the effectiveness of ciplukan stem water extract on the level of malondialdehyde of the mandibular bone in white rats of the post-wistar strain ovariectomy. Twenty-four mice were randomly divided into 6 groups with 4 mice each, namely 3 control groups and 3 treatment groups of mice given an extract dose of 500 mg/kgBB, 1,500 mg/kgBB, and 2,500 mg/kgBB for 4 weeks. MDA levels were calculated by thiobarbituric acid (TBA) test and read with a spectrophotometer, kemudian made MDA work curve. The results showed that the increase in MDA levels could be inhibited by the administration of a dose of 500 mg/kg BB, while a dose of 1500 mg/kg BB 2500 mg/kg BB could improve MDA levels close to normal. There was a strong correlation with a negative direction between the dose of ciplukan stem water extract and the MDA level of the mandibular bone (r=--0.507). The conclusion of this study is that the administration of ciplukan stem water extract can reduce the MDA level of mandibular bone in white rats of wistar strain after oophorectomy.